Environmental Reviews and Case Studies: Cultural Heritage, Community Engagement, and Environmental Impact Assessment in Australia. (1st September 2016) - Lilley, Ian
Abstract : This brief article sketches the current situation regarding cultural heritage, community engagement, and environmental impact assessment in Australia. The country is by no means perfect when it comes to heritage management in the impact-assessment process. Yet, practitioners have evolved a set of common understandings concerning social value and community engagement that characteristically (though, of course, not inevitably) produce mutually-acceptable outcomes for all stakeholders. These understandings rest largely on the internationally-renowned "Burra Charter, " which applies to all cultural heritage in Australia, but are given added legal weight with regard to Indigenous heritage by Native Title legislation giving Aboriginal and Torres Strait Islander people a significant say in land use. The centrality of social value and community engagement is clear in the codes of ethics of professional organizations managing heritage in impact assessment, such as the Australian Archaeological Association and the Australian Association of Consulting Archaeologists Inc.